Drug Weaponry to Fight Against SARS-CoV-2 - Cabezón, Elena; Arechaga, Ignacio (Frontiers in Molecular Biosciences, 2020)
The current outbreak of SARS-CoV-2 virus has caused a large increase in mortality and morbidity associated with respiratory diseases. Huge efforts are currently ongoing to develop a vaccine against this virus. However, alternative approaches could be forseen in the fight against this disease. Among other strategies, structural-based drug design could be an effective approach to generate specific molecules against SARS-CoV-2, thus reducing viral burden in infected patients. Here, in addition to this structural approach, we also revise several therapeutic strategies to fight against this viral threat. Furthermore, we report ACE-2 genetic polymorphic variants affecting residues involved in close contacts with SARS-CoV-2 that might be associated to different infection risks. These analyses could provide valuable information to predict the course of the disease.